Combined in situ XAS and DFT studies on the role of Pt in zeolite-supported metal catalysts for selective n-hexane isomerization. (15th April 2022) - Injongkol, Yuwanda; Khemthong, Pongtanawat; Yodsin, Nuttapon; Wongnongwa, Yutthana; Sosa, Narongrit; Youngjan, Saran; Butburee, Teera; Rungtaweevoranit, Bunyarat; Kiatphuengporn, Sirapassorn; Wittayakun, Jatuporn; Roessner, Frank; Jungsuttiwong, Siriporn
Graphical abstract: Highlights: Combined experimental and DFT studies can elucidate the role of Pt catalyst. Adding Pt atom into HY zeolite facilitates C‒C cleavage and formation processes. The isomerization on Pt-HY catalyst required a remarkably low barrier of 0.97 eV. The Pt-HY catalyst is more selective towards 2MP than 3MP. Abstract: In this study, we used several in situ, and spectroscopy analyses to investigate the roles of platinum (Pt) in zeolite-supported Pt catalysts for selective n -alkane isomerization. HY zeolites were synthesized using the rice husk silica and impregnated with Pt precursor by incipient wetness impregnation. Typically, HY zeolites have proved to be active hydrocarbon cracking catalysts. The particular challenge is to find an effective catalyst, which favors the isomerization of n -alkanes without too much cracking. In this work, adding Pt atoms to HY zeolite provides an enhanced multifunctional catalyst for converting n -alkanes to branched hydrocarbons. To understand the effect of Pt, we further investigated the reaction mechanism of n -hexane isomerization to 2–methylpentane (2MP) and 3-methylpentane (3MP) by DFT simulations, using a cluster of 30T HY zeolite modeled through B3LYP + 3D calculations. We found that, at 450 °C, the isomerization on Pt-HY gives higher cracking products. Decreasing temperature to 300 °C yielded greater selectivity of branched hydrocarbons. In addition, DFT calculations demonstrate that the 2MP production via route A1 (C3-C4 bond activation) and a rate-determining step of 0.97 eV proved more thermodynamically and kinetically favorable than the 3MP product. This agrees well with our experimental observations. Consequently, the presence of Pt on the HY zeolite plays an essential role in both CC forming and breaking. Finally, the Pt–HY zeolite is an efficient catalyst for petroleum production, improving the octane number for catalytic performance and product selectivity by isomerizing straight-chain alkanes to their branched chain isomers.